A New Species of Lactarius subg. Lactarius (Russulaceae) from Baiyun Mountain, China - Huang, Xiao-Xia; Lin, Zhi-Jun; Li, Si-Duo; Qiu, Li-Hong (Phytotaxa, 2022)
A new species of Lactarius subg. Lactarius from Baiyun Mountain, Guangdong Province in southern China is described based on phylogeny of the internal transcribed spacer (ITS) and morphological analyses. Lactarius baiyunensis sp. nov. is characterized by a light brown to white, azonate or inconspicuously zonate pileus, irregular brownish spots on the stipe, latex unchanging in color, small globose to subglobose basidiospores with pronounced ornamentation, absence of cheilocystidia and an ixotrichoderm for a pileipellis. The new species is presented with illustrated description, and comparisons of morphology and phylogeny are made with closely related species.